Karakteristik Buah Rambutan pada Suhu Dingin dengan Kemasan Terbuka dan Tertutup - Ignasius Edward Ileng; Luh Suriati; Ni Made Ayu Suardani Singapurwa; I Gede Pasek Mangku (GEMA AGRO, 2020)
Rambutan is one of the potential fruits to be developed. It is because Rambutan contains many compounds that are beneficial to the body. Rambutan is easily damaged if stored at room temperature. To maintain the quality and shelf life of rambutan requires a variety of techniques one of which is the temperature setting during storage. The damage of Rambutan starts from damage to the skin and fruit hair. Fresh-Cut is one way that rambutan fruit can be consumed in a longer time. Freshcut is a treatment by removing parts that are not consumed in the fruit through the process of stripping, cutting, slicer and so forth. This research was conducted using the complete random design method of factorial and 2 repeats. The first factor includes the long storage of Rambutan fruit consists of 6 levels, namely 0, L, 2, 3, 4, 5, 6. The second factor is the storage temperature of Rambutan fruit consists of two levels of cold temperature (7-12) ï‚°C and freezing temperature ((-4)-0)ï‚°C. Observations conducted objectively include: moisture content, pH, TSS, Vitamin C. Whole fruit storage and fresh-cut rambutan preferably at a temperature of 7-12ï‚°C with a closed packaging. Whole fruit even though the skin has changed brown but the fruit characteristics in it is still good until Day 6, while the best characteristic of Fresh-cut Rambutan until day 3.